Periodismo preventivo y el aporte a la construcción del conocimiento en los medios televisivos del cantón Latacunga. - Ortega Granda, Klever Mauricio (2018)
The present research focuses on identifying how the television media of the Canton Latacunga (Color TV, ELITE Tv, MICC) resort to the use of preventive journalism, with regard to the informational content, taking into account that this type of journalism is relevant, because it helps to prevent crises or disasters that may affect society in general and, therefore, to its development in the same. This recognition is achieved, thanks to the scientific and technical substantiation of the issue raised, where the aim is to define each of the basic categories identified for development, taking into account that this project tries to solve the existing problem, identifying, recognizing and defining the limited knowledge present in the local media about the preventive journalism and its contribution in the knowledge construction. This communicative proposal to this journalistic genre is taken into account, stressing its importance to avoid any kind of disasters both natural and social, affecting society and its development, for this reason that through the use of a qualitative-quantitative approach and techniques such as the survey and interview, we will be able to obtain favorable results for the investigation. In this sense, this research will benefit the community latacungueña to be informed of possible damage to which they may be exposed before, during and after a crisis or conflict present in society, all of this thanks to the transmission of preventive programming on the part of the local media.